Lack of Association between Gender, Age, and Severity of Periodontitis in Type 2 Diabetic Patients: A Cross-Sectional Study in Banjarbaru, Indonesia - Naning Kisworo Utami; Rasuna Ulfah; Bunga Nurwati; Hammad (Postgraduate, University of Mataram, 2025)
Periodontal disease is more prevalent and severe in patients with type 2 diabetes mellitus. This study aimed to describe periodontal status and examine its association with gender and age among diabetic patients enrolled in the Prolanis program. A cross-sectional analytical survey was conducted on all 65 Prolanis participants with confirmed type 2 diabetes mellitus at Banjarbaru Selatan Community Health Center, Indonesia. Periodontal status was assessed using the Community Periodontal Index of Treatment Needs (CPITN). Severity was dichotomized as not severe (score 0–2) and severe (score 3–4). Associations with gender and age groups were tested using chi-square tests (α = 0.05). Participants were predominantly female (84.6%) with a mean age of 58 years. Severe periodontitis (pocket ≥4 mm) was found in 63.1% of patients. No significant association was observed between periodontal disease severity and gender (p = 0.733) or age group (p = 0.114). A high burden of moderate-to-severe periodontitis exists among diabetic patients in the Prolanis program, irrespective of gender or age. Regular periodontal screening and integrated diabetes–oral health management are strongly recommended.